Speaking to Inspire: A Rhetorical Analysis of Jim Kwik’s Inspirational Speech - Gawi, Abdul; Waluyo, Untung; Fitriana, Eka; Soepriyanti, Henny (Journal of English Education Forum (JEEF), 2025)
This research explores the rhetorical strategies employed by Jim Kwik, a motivational speaker and memory coach, focusing on his YouTube and podcast content. Grounded in classical and digital rhetoric theories, this study investigates how Kwik constructs digital ethos, pathos, and logos through verbal performance, sound cues, and narrative techniques. The article integrates Cicero's classical oratory principles, Aristotle's persuasive appeals, and Eyman's digital rhetoric framework to analyze Kwik's communication methods. Using a qualitative narrative approach and thematic analysis, five podcast episodes from "Kwik Brain" (2022–2024) were analyzed to assess how rhetorical devices engage audiences and promote cognitive empowerment. The study finds that Kwik's multimodal rhetoric is characterized by accessible logic, emotional storytelling, and personal credibility. His hybrid use of motivational and commercial discourse highlights both the transformative potential and ethical ambiguity of digital persuasion. This research offers insights into how digital rhetoric operates in contemporary motivational media and provides a framework for evaluating persuasive communication in informal learning environments.